Keep this, toss that : unclutter your life to save time, money, space, and sanity - Novak, Jamie (Reader's Digest, the Reader's Digest Association, Inc., 2015)
"Quick answers to the one key question everyone needs to answer in order to get organized and save their time, money, space, and sanity: "Should I keep or toss this?" You've finally decided to clean out your kitchen cabinet. You bravely, yet slowly, open the cabinet door knowing that food storage containers are going to come pouring out like an erupting volcano. You tediously pick them up and sort them by shape and size; you're positive you don't need all twenty-two containers, but you're not sure which ones you should toss. All of a sudden the tiny sized salad dressing container seems equally as important as the oversized casserole container. You can't decide what to toss so you just stack them back in the cabinet and shut the door quickly. The 1.5 million chronically disorganized Americans need just one thing: they need help making decisions about what to keep and what to toss. Americans spend approximately $168 billion annually to get more organized; one of their first purchases should be Keep This, Toss That! Have you ever wondered how long sunscreen is good for? Will you regret it tomorrow if you toss all your flower vases? How many bath towels do you need to keep in case you have company? Does Worcestershire sauce go bad? Is it worth hanging on to the boxes all your plates and glasses came in? And exactly how long do you need to hang onto those bank statements? The answer to all these questions and many more can be found in Keep This, Toss That. Smartly organized in four easy to reference sections: 1. Home/Living 2. Personal/Clothing 3. Storage/Hobby 4. Office/Paper Keep This, Toss That features illustrated Keep/Toss checklists that show you at a glance exactly what you need--and what you can safely toss, regret-free. The book also includes quick tips on clever storage solutions, tools and utensils that can do double-duty, and advice on how to customize the lists for your individual needs"--